Microtextural characteristics of adularia in banded quartz veins from the Midas low-sulfidation epithermal deposit, Nevada - Lauren R. Terry; Thomas Monecke; T. James Reynolds; Filip Kasprowicz; Katharina Pfaff (Mineralium Deposita, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Heat-Induced metabolomic shifts in cold-adapted Ulva holobiont from Antarctica (Potter Cove, South Shetland Islands) - Marine Vallet; Fatemeh Ghaderiardakani; Maria Liliana Quartino; Filip Kaftan; Georg Pohnert; Thomas Wichard (Journal of Applied Phycology, 2026)
The algal holobiont, a symbiotic association of algae and bacteria, provides strategies to cope with environmental stresses. Bacteria associated with the green alga Ulva (Chlorophyta) are known to produce essential bioactive compounds, such as thallusin and ectoine, that promote algal growth; however, the metabolic mechanisms underlying stress adaptation in these mutualistic interactions remain poorly understood. Specifically, research is still emerging on the metabolome of cold-adapted Ulva holobionts from remote regions, such as Antarctica, and on how the metabolic profiles respond to environmental changes. This study thus examined heat-induced changes in osmolyte and zwitterion molecules bearing balanced positive and negative charges in Ulva sp. (strain FSU-UPC-109) collected from the Antarctic ecosystem of Potter Cove, South Shetland Islands, and maintained under laboratory conditions at 2°C. Using ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC–HRMS), we identified highly polar low molecular weight compounds, including cysteinolic acid, ectoine, glutamine, glycerol, and proline. Their spatial distribution on the thallus and rhizoids was determined with atmospheric-pressure matrix-assisted laser desorption/ionization imaging (AP–SMALDI). We demonstrated that the metabolite levels shifted significantly under heat stress, indicating that environmental temperature changes strongly influence the metabolome of Antarctic Ulva seaweed and may support their capacity for thermal acclimation. Graphical abstract Using high-resolution (imaging) mass spectrometry, we studied the heat-induced changes in abundance of the osmolytes and zwitterions, molecules bearing balanced positive and negative charges, in Ulva collected from the Antarctic ecosystem of Potter Cove, South Shetland Islands.

Defining the Cis-Regulatory Elements of SCN1A in GABAergic Interneurons - Joachim Luginbühl; Anika V. Prabhu; Chi Wai Yip; Yoshinari Ando; Julio Leon; Kayoko Yasuzawa; Chung Chau Hon; Jonathan Moody; Filip Roudnicky; Thomas Kremer; Jay W. Shin (Molecular Neurobiology, 2025)

Synergistic pharmaceutical interactions with nanoscale iron nitrides and natural organic matter - Veronika Veselská; Josef Kašlík; Diego Baragaño; Anaëlle Simonneau; Thomas Thiebault; Martin Petr; Jan Filip; Jean-Sébastien Moquet; Gildas Ratié (Chemical Engineering Journal, 2025)

Exploring marine microbial diversity: an overview of representative sampling strategies - Zrinka Ljubešić; Marija Gligora Udovič; Donata Overlingė; Filip Grgurević; Füsun Akgül; Ariola Bacu; Ana R. Díaz-Marrero; Dragana Drakulović; Stefano Fazi; Susana P. Gaudêncio; Anamarija Kolda; Lucie Novoveska; et al. (Frontiers in Marine Science, 2025)
The assessment of marine microbial biodiversity is crucial for determining either the environmental status (ecological or biodiversity research) or as a first step in the biodiscovery process (biotechnological research). Regardless of the research purpose, the first step in a biodiversity assessment is sampling, which can range from ad hoc sampling expeditions to long-term monitoring campaigns. In spite of its demands for funds, infrastructure, expertise, equipment, and personnel, sampling is often not adequately planned. This results in increased likelihood for biased sampling, which can lead to misinterpretation of results, omission of valuable specimens and an unrepresentative collection of stored samples, all particularly important for the assessment of microbial biodiversity. For these reasons, we are proposing a conceptual framework to assist in better preparation of sampling, consisting of pre-sampling, sampling and post sampling steps. The manuscript guides the reader through all the necessary steps, regardless of the sampling habitat (from water column to sediment), the sampling techniques and the preservation and storage approaches including culture and biorepositories. Such a harmonized approach can be of benefit for (i) researchers in the field of ecology/biotechnology, (ii) industrial companies requiring information on the providers and availability of data, and (iii) governance structures and funders, in the light of open science principles.

Effects of resistance-based training and polyphenol supplementation on physical function, metabolism, and inflammation in aging individuals - Mathias Flensted-Jensen; Cecilie Moe Weinreich; Ann-Sofie Kleis-Olsen; Filip Hansen; Nadia Stenner Skyggelund; Jeppe Rahbek Pii; Ryan Whitlock; Marie-Louise Brødsgaard Abrahamsen; Thomas Isbrandt Petersen; Anders Karlsen; Dace Reihmane; Flemming Dela (GeroScience, 2025)
Aging is associated with declines in muscle mass, strength, aerobic capacity, and metabolic health, accompanied by increased low-grade inflammation. The purpose of this study was to assess the effects of 12 weeks of resistance training (RT) combined with minimal high-intensity interval training (HIIT), with or without polyphenol supplementation, on muscular, cardiovascular, metabolic, and inflammatory adaptations in healthy older adults. Forty-one men and women aged 55–70 years ingested either polyphenol supplementation or placebo for 30 days, then underwent 12 weeks of supervised RT combined with once-weekly HIIT, continuing polyphenol supplementation or placebo throughout. The training intervention increased whole-body and thigh lean mass, vastus lateralis cross-sectional area, type II fiber size, and muscle and functional strength (all p < 0.001). Maximal oxygen uptake significantly increased ( p = 0.0001), accompanied by reductions in heart rate and plasma lactate during submaximal exercise, as well as increases in total blood volume and hemoglobin mass ( p < 0.05). Training led to reductions in respiratory exchange ratio and plasma cortisol during exercise, which, together with decreased cholesterol levels and trends toward increased peak fat oxidation, may suggest enhanced substrate utilization. Polyphenols alone lowered cholesterol levels but had no other effects. Although no changes were observed in basal systemic or muscle inflammation, the exercise intervention attenuated the acute exercise-induced inflammatory responses of IL-10, IFN-γ, and TNF-α ( p < 0.05). These results indicate that a combined RT and minimal HIIT program improves muscular, aerobic, and metabolic health, and may improve inflammatory regulation in aging adults.

Surface temperature changes indicate disease onset after pulmonary murine corona virus infection, but do not constitute a humane endpoint - Rebecca Nistelberger; Patrizia Gibler; Thomas Filip; Manuel Salzmann; Boris Hartmann; Bruno K. Podesser; Roberto Plasenzotti; Philipp J. Hohensinner; Julia B. Kral-Pointner (Veterinary Research Communications, 2025)
Mouse models are important contributors for understanding the immune system during infections. Objective parameters help to assess the course of infection and guarantee animal welfare. In this study we analyzed if surface temperature measured via thermal imaging of the dorsal area is a suitable marker to evaluate animal wellbeing during murine coronavirus (MCoV) infection. Infected BALB/c mice displayed severe symptoms whereas C57BL/6 mice were less affected. In BALB/c animals, temperature increased from 27.1 °C to 28.4 °C within 24 h with levels remaining slightly elevated over the observation period. In contrast, a decrease in body weight was consistent through the period with 60% of the animals reaching the previously set termination point of 20% weight loss ( n = 6). Also, C57BL/6J animals showed a significant temperature increase from 27.1 °C to 28.4 °C within 24 h and a significant weight loss over time with two out of ten reached weight loss end point. However, temperature and weight changes were not related in individual animals. In contrast to temperature values, body weight clearly set a trajectory towards early termination. Taken together, our data indicate that superficial temperature did not serve as a predictive parameter for defining humane end points, but indicate disease onset after pulmonary virus infection.

Trends in mercury, lead and cadmium concentrations in 27 European streams and rivers: 2000–2020 - Karin Eklöf; Claudia von Brömssen; Brian Huser; Staffan Åkerblom; Algirdas Augustaitis; Hans Fredrik Veiteberg Braaten; Heleen A. de Wit; Thomas Dirnböck; David Elustondo; Ulf Grandin; Adéla Holubová; Sirpa Kleemola; et al. (Environmental Pollution, 2024)

A structured approach for the compliance analysis of battery systems with regard to the new EU Battery Regulation - Sönke Hansen; Tom Rüther; Mark Mennenga; Christoph Helbig; Gregor Ohnemüller; Filip Vysoudil; Constantin Wolf; Bernd Rosemann; Sandra Pavón; Alexander Michaelis; Thomas Vietor; Frank Döpper; et al. (Resources, Conservation and Recycling, 2024)

Is EGD Needed in all Patients after Suicidal or Exploratory Caustic Ingestions? - Michael Levine; Yaron Finkelstein; William J. Trautman; Dazhe Cao; Evan Schwarz; Ari Filip; Leanne Cook; Sameer Arbussattar Pathan; Cherie Obilom; Jim Liu; Joseph Yanta; Neta Cohen; et al. (Journal of Medical Toxicology, 2024)

Analysis and modelling of single domain core-shell (αFeNi/chromite) nanoparticles emitted during selective laser melting, and their magnetic remanence - Richard Dvorsky; Jana Kukutschová; Marek Pagáč; Ladislav Svoboda; Zuzana Šimonová; Kateřina Peterek Dědková; Jiří Bednář; Rafael Gregorio Mendes; Dalibor Matýsek; Ondřej Malina; Jiří Tuček; Zuzana Vilamová; et al. (Journal of Cleaner Production, 2023)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Influence of Cation Transporters (OCTs and MATEs) on the Renal and Hepatobiliary Disposition of [11C]Metoclopramide in Mice - Irene Hernández-Lozano; Severin Mairinger; Michael Sauberer; Johann Stanek; Thomas Filip; Thomas Wanek; Giuliano Ciarimboli; Nicolas Tournier; Oliver Langer (Pharmaceutical Research, 2021)
Purpose To investigate the role of cation transporters (OCTs, MATEs) in the renal and hepatic disposition of the radiolabeled antiemetic drug [ 11 C]metoclopramide in mice with PET. Methods PET was performed in wild-type mice after administration of an intravenous microdose (<1 μg) of [ 11 C]metoclopramide without and with co-administration of either unlabeled metoclopramide (5 or 10 mg/kg) or the prototypical cation transporter inhibitors cimetidine (150 mg/kg) or sulpiride (25 mg/kg). [ 11 C]Metoclopramide PET was also performed in wild-type and Slc22a1/2 (−/−) mice. Radiolabeled metabolites were measured at 15 min after radiotracer injection and PET data were corrected for radiolabeled metabolites. Results [ 11 C]Metoclopramide was highly metabolized and [ 11 C]metoclopramide-derived radioactivity was excreted into the urine. The different investigated treatments decreased (~2.5-fold) the uptake of [ 11 C]metoclopramide from plasma into the kidney and liver, inhibited metabolism and decreased (up to 3.8-fold) urinary excretion, which resulted in increased plasma concentrations of [ 11 C]metoclopramide. Kidney and liver uptake were moderately (~1.3-fold) reduced in Slc22a1/2 (−/−) mice. Conclusions Our results suggest a contribution of OCT1/2 to the kidney and liver uptake and of MATEs to the urinary excretion of [ 11 C]metoclopramide in mice. Cation transporters may contribute, next to variability in the activity of metabolizing enzymes, to variability in metoclopramide pharmacokinetics and side effects.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Isolation and characterisation of 14 novel microsatellite markers through Next Generation Sequencing for the commercial Atlantic seabob shrimp Xiphopenaeus kroyeri - Thomas R. H. Kerkhove; Bart Hellemans; Marleen De Troch; Annelies De Backer; Filip A. M. Volckaert (Molecular Biology Reports, 2019)

The neural correlates of flow experience explored with transcranial direct current stimulation - Martin Ulrich; Johannes Niemann; Markus Boland; Thomas Kammer; Filip Niemann; Georg Grön (Experimental Brain Research, 2018)

Erratum to: Ethylene Controls Adventitious Root Initiation Sites in Arabidopsis Hypocotyls Independently of Strigolactones - Amanda Rasmussen; Yuming Hu; Thomas Depaepe; Filip Vandenbussche; Francois-Didier Boyer; Dominique Van Der Straeten; Danny Geelen (Journal of Plant Growth Regulation, 2018)

Ethylene Controls Adventitious Root Initiation Sites in Arabidopsis Hypocotyls Independently of Strigolactones - Amanda Rasmussen; Yuming Hu; Thomas Depaepe; Filip Vandenbussche; Francois-Didier Boyer; Dominique Van Der Straeten; Danny Geelen (Journal of Plant Growth Regulation, 2017)

Marine‐terminating glaciers sustain high productivity in Greenland fjords - Lorenz Meire; John Mortensen; Patrick Meire; Thomas Juul‐Pedersen; Mikael K. Sejr; Søren Rysgaard; Rasmus Nygaard; Philippe Huybrechts; Filip J. R. Meysman (Global Change Biology, 2017)
Accelerated mass loss from the Greenland ice sheet leads to glacier retreat and an increasing input of glacial meltwater to the fjords and coastal waters around Greenland. These high latitude ecosystems are highly productive and sustain important fisheries, yet it remains uncertain how they will respond to future changes in the Arctic cryosphere. Here we show that marine‐terminating glaciers play a crucial role in sustaining high productivity of the fjord ecosystems. Hydrographic and biogeochemical data from two fjord systems adjacent to the Greenland ice sheet, suggest that marine ecosystem productivity is very differently regulated in fjords influenced by either land‐terminating or marine‐terminating glaciers. Rising subsurface meltwater plumes originating from marine‐terminating glaciers entrain large volumes of ambient deep water to the surface. The resulting upwelling of nutrient‐rich deep water sustains a high phytoplankton productivity throughout summer in the fjord with marine‐terminating glaciers. In contrast, the fjord with only land‐terminating glaciers lack this upwelling mechanism, and is characterized by lower productivity. Data on commercial halibut landings support that coastal regions influenced by large marine‐terminating glaciers have substantially higher marine productivity. These results suggest that a switch from marine‐terminating to land‐terminating glaciers can substantially alter the productivity in the coastal zone around Greenland with potentially large ecological and socio‐economic implications.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Evaluating life‐history strategies of reef corals from species traits - Emily S. Darling; Lorenzo Alvarez‐Filip; Thomas A. Oliver; Timothy R. McClanahan; Isabelle M. Côté (Ecology Letters, 2012)
Classifying the biological traits of organisms can test conceptual frameworks of life‐history strategies and allow for predictions of how different species may respond to environmental disturbances. We apply a trait‐based classification approach to a complex and threatened group of species, scleractinian corals. Using hierarchical clustering and random forests analyses, we identify up to four life‐history strategies that appear globally consistent across 143 species of reef corals: competitive, weedy, stress‐tolerant and generalist taxa, which are primarily separated by colony morphology, growth rate and reproductive mode. Documented shifts towards stress‐tolerant, generalist and weedy species in coral reef communities are consistent with the expected responses of these life‐history strategies. Our quantitative trait‐based approach to classifying life‐history strategies is objective, applicable to any taxa and a powerful tool that can be used to evaluate theories of community ecology and predict the impact of environmental and anthropogenic stressors on species assemblages.

Public policies as institutions for sustainability: potentials of the concept and findings from assessing sustainability in the European forest-based sector - Thomas Vogelpohl; Filip Aggestam (European Journal of Forest Research, 2012)

Aspects of phytoremediation for chromium contaminated sites using common plants Urtica dioica, Brassica napus and Zea mays - Khaled Mahmud Shams; Gottfried Tichy; Axel Fischer; Manfred Sager; Thomas Peer; Ashtar Bashar; Kristina Filip (Plant and Soil, 2010)